The Goldilocks view: Support and skepticism of the impacts and pace of unconventional oil and gas development in the Bakken Shale of the United States. (December 2020) - Ulrich-Schad, Jessica D.; Larson, Eric C.; Fernando, Felix; Abulbasher, Abdelrahim
Highlights: Examines views on continued oil/gas development within the mini-boom/bust context. Many residents see oil/gas booms as positive, but also prefer a slower pace of growth. Trust in the oil/gas industry to address spills is needed for support of pipelines. Abstract: Residents of rural communities with histories of booms and busts in natural resource extraction often have divergent and simultaneously complex views on whether continued development of such industries is desirable. For instance, while many residents appreciate the economic benefits generated by these industries, some are also skeptical about disruptions resulting from expanding or continuing resource extraction. We use social representation theory and a mini-boom/bust framework to examine Bakken Shale residents' perceptions of current and continued development of the oil and gas industry, including the role of industrial legacy and environmental concerns. Data from our 2016 survey indicates that about one in four residents see oil and gas development as positive for their community, but at the same time, felt relief that the most recent boom slowed in pace. We refer to this as the Goldilocks View of Development and see it as evidence of support for a mini-bust. In terms of continued development of the industry as represented by the construction of the Dakota Access Pipeline, we found a high level of support for construction, and that political party, belonging to a local organization, and trust in industry to address spills are key predictors of such support. As natural resource dependent communities such as those in the Bakken Shale continue to experience unconventional oil and gas development in a mini-boom/bust context, it is important to understand residents' perceptions so that state and local governments can develop policies towards the industry that address local concerns.